Studies on Synthesis, Characterization of Modified Phenol Formaldehyde Resin and Metal Adsorption of Modified Resin Derived From Lignin Biomass - Arasaretnam, Selladurai; Kirudchayini, T. (Ital Publication, 2019)
This study was related to development of economically viable method of extraction of lignin from saw dust in order to produce lignin modified phenolic resin and ecofriendly adhesives (bio-based resin). This study cover to improve the mechanical properties by modification of phenol formaldehyde resole resin using some additives such as boric acid, sulfuric acid and lignin biomass. The synthesis and metal adsorption capacity of resin derived from lignin biomass were explored. Lignin sample was extracted from sawdust of Acacia sp. collected from Batticaloa region by alkali extraction method called delignification process. Qualitative tests were carried out on the extracted alkali lignin and it was used to prepare modified resin. Resin synthesized by using lignin substitution phenol and allowed to condensation reaction in the presence of sodium hydroxide. Boron-modified phenol formaldehyde resin was prepared by using boric acid with formalim method. The above reaction was performed for four hours by refluxing with toluene. Which was produced a high viscous massive resin with 90% yield. The absorbtion peak of B-O bond at 1362cm-1 was observed at IR spectra. Rise in solid mass content leads to produce smooth resin surface without causing cracks and bubbling. Phenol formaldehyde resin was modified into their sulfonated forms to increase their ion exchange capacity, since the ion exchange capacity of virgin resin was found to be zero. Conductivity property shown by sulfonated resin(121mS/cm). The synthesized Lignin based PF resin was used to study the metal adsorption capacity of Cd2+ in aqueous solution. The adsorption capacity of heavy metal Cd2+ ion shown by lignin modified resin (55%) and lignin (86%). In this study sawdust lignin could be best substitution for phenol in synthesis of Phenol-Formaldehyde resin. It’s better due to their sustainability, environmental control, low production cost and their ability to adsorb heavy metals. Phenolic resin was modified with boric acid to improve thermal resistance property and to get smooth resin surface.